Lead-free organic–inorganic hybrid perovskite heterojunction composites for photocatalytic applications. Issue 13 (31st May 2017) - Zhang, Weining; Zhao, Qingguo; Wang, Xiaohong; Yan, Xiaoxia; Xu, Jiaqiang; Zeng, Zhigang
Abstract : Heterojunction structured MASnI3 /TiO2 photocatalysts (MA represents CH3 NH3 + ) are prepared via a facile wet-chemical method and characterized by various techniques. Abstract : Heterojunction structured MASnI3 /TiO2 photocatalysts (MA represents CH3 NH3 + ) are prepared via a facile wet-chemical method and characterized by various techniques. The characterization demonstrates the formation of a heterojunction structure and the good crystallinity of MASnI3 /TiO2 (1 : 9) (mass ratio of MASnI3 and TiO2 is 1 : 9). Moreover, the results also display the improved visible light absorption of MASnI3 /TiO2 (1 : 9) and low recombination of photoinduced carriers. As a result, MASnI3 /TiO2 (1 : 9) could completely degrade rhodamine B (97%) in 40 min, which has higher photocatalytic ability than pure MASnI3 and pure TiO2 . The improved photocatalytic activity could be ascribed to the improved light harvesting ability and easy transfer of photogenerated carriers of the materials generated by the formation of a heterojunction structure and the suitable energy band position between MASnI3 and TiO2 . In particular, coupling of MASnI3 and TiO2 could also avoid oxidation and hydrolysis of MASnI3 so that the long-term stability of the composite could be efficiently maintained. It is the first report on MASnI3 and TiO2 composites being used as photocatalysts for dye degradation. A possible mechanism for the enhancement of photocatalytic activity under light irradiation is also proposed.